2011
DOI: 10.1007/s10764-011-9502-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Urine Washing Behavior in Tufted Capuchins (Cebus apella)

Abstract: Urine washing is a common behavior in strepsirrhine and platyrrhine primates, but its function is still poorly understood. We investigated the factors influencing urine washing behavior in 2 captive groups of tufted capuchins (Cebus apella). Urine washing was affected by group membership (subjects in the 2 groups urine washed at different rates) and was negatively related to age, but was not influenced by sex or dominance rank. Females urine washed less when in estrus, and the presence of an estrous female did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 14 publications
2
18
1
Order By: Relevance
“…Although scent marking in New World primates has been mainly investigated in relation to territoriality with little data available regarding its function of advertising female reproductive state (see Heymann, 2006), a study in cotton-top tamarins, a species that lacks behavioral indicators of the periovulatory period, provided evidence for a direct olfactory cue of ovulation that affects male sexual behavior (Ziegler et al, 1993a). Recent studies in both robust and gracile capuchins, however, have found no evidence in support of a potential function of scent marking within socio-reproductive contexts (Carnegie et al, 2005;Schino et al, 2011).…”
Section: )mentioning
confidence: 99%
“…Although scent marking in New World primates has been mainly investigated in relation to territoriality with little data available regarding its function of advertising female reproductive state (see Heymann, 2006), a study in cotton-top tamarins, a species that lacks behavioral indicators of the periovulatory period, provided evidence for a direct olfactory cue of ovulation that affects male sexual behavior (Ziegler et al, 1993a). Recent studies in both robust and gracile capuchins, however, have found no evidence in support of a potential function of scent marking within socio-reproductive contexts (Carnegie et al, 2005;Schino et al, 2011).…”
Section: )mentioning
confidence: 99%
“…Urine washing in particular has been linked to social situations, especially in the context of submission (Miller et al, 2007), although other functions have also been proposed (e.g. Roeder and Anderson, 1991; Campos et al, 2007; Schino et al, 2011). Interference with subjects’ scent is consistent with the current results: group members reacted to potentially missing indicators of social status by displaying their own dominance status towards subjects and, not necessarily independently, refrained from reaffirming social bonds through affiliative displays.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous hypotheses have been offered to explain urine-washing by primates, including non-signalling functions such as thermoregulation (Schmidt & Seitz, 1967;Schwartz & Rosenblum, 1985;Roeder & Anderson, 1991;Heymann, 1995), moistening hands to improve grip (Castell & Maurus, 1967;Welker, 1973;Harcourt, 1981), stress-induced displacement behaviour (DuMond, 1968;Andrew & Klopman, 1974), and scent-trails for orientation (Eibl-Eibesfeldt, 1953;Milton, 1975); and signalling functions such as marking the home range (Charles-Dominique, 1977), asserting dominance (Perry, 1998;Campos et al, 2007), and communicating reproductive status (Hennessy et al, 1978;Milton, 1985;Boinski, 1992;Miller et al, 2008). None of these studies has examined the question using rigorous statistical methods that control for confounding variables (but see Schino et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…have produced no conclusive answers regarding its function, though they agree that the behaviour is likely multifunctional and exhibits strong seasonal fluctuations (Robinson, 1979;Perry, 1998;Carnegie et al, 2005;Campos et al, 2007). Some research on captive C. apella suggests that urine-washing may be used for thermoregulation (Roeder & Anderson, 1991), but two recent studies oppose this claim (Miller et al, 2008;Schino et al, 2011). There is some qualitative evidence that urine-washing in C. apella is associated with receiving aggression and that alpha males urine-wash in response to sexual solicitations from females (Miller et al, 2008), but these findings could not be replicated in a subsequent study (Schino et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation